Fertilization, hatching, and survival rates of Triploid purebred native Catfish (Clarias macrocephalus Gunther Clarias macrocephalus Gunther induced ny heat shock. - Dayo, Aura Bree C.
Catfish is considered to be one of the world's most valuable fishes in aquaculture., The populations of native catfish, clarias macrocephalus Gunther, are fast declining due to its slow growth and poor breeding activities. Because native catfishes are highly valued for their meat quality but are poorly disregarded for their longer culture period, it is hope of this study to arrive at genralized schemes for triploidy induction n catfishes, thereby opening doors to more extensive research on catfish triploidy in the future. This special problem was conducted to compare performance of triploid native catfish Clarias macrocephalus female X Clarias macrocephalus male induced by heat shock with normal diploid catfish and to specifically compare fertilization, hatching, and survival rates. Heat schock was carried out at 35 degrees centigrade, 37 degrees centigrade, and at 39 degrees centigrade. Based on experimental results, normal diploid catfishes have better performance, as determined by numerical data from percent fertilization, hatching, and survival . Among heat shock treatments, the most optimum temperature for fertilization is 35 degrees centigrade to 37 degrees centigrade; for hatching, 35 degrees centigrade; for survival at day 2, 37 degrees centigrade; and for survival at day 5, 39 degrees centigrade.